Stable isotopes in ecology and environmental science (Blackwell Pub., 2007)
This book highlights new and emerging uses of stable isotope analysis in a variety of ecological disciplines. While the use of natural abundance isotopes in ecological research is now relatively standard, new techniques and ways of interpreting patterns are developing rapidly. The second edition of this book provides a thorough, up-to-date examination of these methods of research.